ANALISIS KUALITAS IKLAN VIDEO DAN EFEKTIFITASNYA SEBAGAI MATERI PEMASARAN PADA PEREMPUAN DI KOTA BATAM: STUDI KASUS PERHIASAN - Veri Hartanto; Deli (BETRIK, 2022)
Advertising is a form of promotion as a marketing medium used in delivering a message from a product offered to consumers. The study was conducted to determine the effectiveness of advertising on jewelry products using the AIDA model (Attention, Interest, Desire, Action) and the MDLC method (Multimedia Development Life Cycle). The population in this study was 608.010 million women in Batam and with a sample of 100 respondents. The study was conducted by distributing questionnaires on social media that were analyzed and data processed using the SPSS application. The results showed that each variable has a positive and effective influence on advertising. The attention variable got a result of 4.41, the interest variable got a result of 4.30, the desire variable got a result of 4.28, and the action variable got a result of 4.22. The overall average score of AIDA got 4.30 which concluded that the advertisements of jewelry products displayed were in a very effective category.